IMPULSIVE BUYING BEHAVIOR IN SOCIAL MEDIA AND E-COMMERCE TO CHRISTMAS STAIN MANDAILING STUDENTS - Rizka Ar Rahmah; Marlina (SEAN Institute, 2022)
This study shows the use of social media which greatly influences impulse buying behavior as an unplanned shopping style, among students. The factors that cause impulse buying are the attitude of spontaneity, excitement and stimulation, synchrony, product animation, satisfaction, and several other factors. The data shows that of the 50 students studied, 39 of them experienced high impulse buying. It is proven by their frequent buying online and without planning. The purpose of this study was to produce a study of consumer behavior, especially impulse buying through social media, especially for STAIN Mandailing Natal students. The method used is descriptive qualitative which describes the condition of impulse buying behavior in students. Data collection techniques are literature study and interviews. Impulse buying behavior also occurs due to stimulation from e-commerce applications that offer interesting goods, resulting in an urge to buy more.